Fernando Pessoa: Fragments of the Sociopolitical Legacy - B. F. Martynov (Ибероамериканские тетради, 2025)
Review of the collection: Fernando Pessoa. Páginas de Pensamento Político (1910–1935). Organização, Introdução e Notas de António Quadros. – Lisboa: Clássica Editora, 2024. – 656 p. (In Portuguese)                The first edition of articles reflecting the political views of Fernando Pessoa (1888– 1935), a famous Portuguese poet and philosopher, was published in Portugal. Hence, it would be interesting to analyze the worldview of this extraordinary person using his own method of «mystical realism». In his articles, written between 1910 and 1935, Fernando Pessoa expressed rather unusual ideas about the state, patriotism, liberty and democracy. He draws a clear distinction between the concepts of «the people» and «the mob» and makes original suggestions on how to reform the Portuguese society based on the national identity, rather than on foreign values. Moreover, Pessoa maintains that the Anglo-Saxon social order, which is present all over the world, has brought to power the «internal foreigners», i.e. liberals and republicans, who have become enemies of their own states. As controversial as the poet’s beliefs may be, one cannot help but agree with his idea that the world is constantly changing; therefore, our view of an individual and society in general should be flexible and subject to reconsideration as well. Even though Fernando Pessoa defended the need for a «meritocratic» system of governance, which he imagined to be a combination of people’s monarchy and new intellectual elite, in the end he failed to propose new ways to create such a system. Still, Fernando Pessoa’s political views expressed in the book are quite relevant today, since it is high time many traditional concepts in political sciences were revised.